Body-Based Units of Measure in Armenian, Russian and Bulgarian Languages - Kamalyan, Arevik (Bulletin of Yerevan University B: Philology, 2024)
In ancient civilizations, the basis for units of measurement was primarily human body parts. Centuries of trade, economic, cultural and political contacts of different countries have also contributed to borrowing, so it is not surprising that the same units of measurement exist in different languages. Some of these units have fallen out of use today (e.g. Armenian "կանգուն" or Russian "локоть"), but most of them continue to be used in colloquial speech, everyday life, and are found in set phrases and idioms.In the article the units of measurement related to body parts in Armenian, Russian and Bulgarian languages are subjected to comparative analysis for the first time. The main purpose of the paper is to identify both common features and differences of the three languages. These differences sometimes become a problem when translating from one language to another, especially when a particular unit of measurement occurs in idioms.
Keywords: ethno-metrology; body-based units of measure; translation of somatic idioms and phrases; units of measurement